BIOGÁS. Transformando vidas en el Caribe colombiano (2024)
As a result of this initiative, FENOGE, in collaboration with the Universidad Antonio Nariño, has contributed to transforming lives in the Colombian Caribbean by implementing biogas as fuel for preparing food for children. This initiative also helps reduce environmental impact by decreasing the consumption of firewood and charcoal and reducing CO2 emissions.